HUBUNGAN KARAKTERISTIK PETANI NENAS DENGAN PENDAPATAN DAN PRODUKSI USAHATANINYA - Elly Rasmikayati; Rani Andriani Budi Kusumo; Bobby Rachmat Saefudin (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Pineapple is one of the mainstay commodities in West Java, but even so, the production still fluctuates, as well as the income of the farmers. Many factors will influence both of them. The purpose of this research is to find out descriptively the production of pineapples and the farmers' income, then related to their characteristics. The method used is secondary data analysis. Data analysis tools used include descriptive statistics and cross-tabulations. The results showed that the most dominant Bogor pineapple farmers were aged 36-45 years, who had graduated from elementary school, also had farming experience of around 1-15 years, the majority of the land area used by farmers was less than 0.5 hectares, and those who owned related to pineapple production and farmers' income is the level of education.